Phytoplankton Composition Considering the Odor Occurrence in Porsuk River (Eskisehir-Turkey) - Demir, Nilsun; Pulatsu, Serap; U. Kirkagac, Mine; Topcu, Akasya; Zencir, Ozge; Fakioglu, Ozden (Asian Journal of Chemistry, 2010)
This study was undertaken with the aim of determining phytoplankton composition and its relation to odor occurrence during the summer months in the Porsuk river. Water samples were taken monthly from five sampling points of the Porsuk river within the boundaries of Eskisehir Province between May and October 2006. Water temperature, dissolved oxygen, pH, conductivity and Secchi depth were measured in situ. Chlorophyll a, ammonia-nitrogen, nitrite-nitrogen, nitrate-nitrogen and orthophosphate concentrations were analyzed. During the research period, 51 phytoplankton species from Bacillariophyta, Chlorophyta, Cyanophyta, Cryptophyta, Pyrrophyta and Euglenophyta were identified. Phytoplankton composition varied from month to month and from upstream to downstream stations. Phytoplankton abundance started to increase in May and decreased in October. It was observed that the occurrence of unpleasant odors in the Porsuk river increased in the summer months when the water temperatures were over 22 ºC. An occasional bad odor was produced by floating algal mats which were basically made up of Oscillatoria sp.